2020
DOI: 10.1177/0042098020907277
|View full text |Cite
|
Sign up to set email alerts
|

Governing urban resilience: Organisational structures and coordination strategies in 20 North American city governments

Abstract: This paper describes how urban resilience governance is structured and coordinated in 20 North American cities (19 US and one Canadian) based on interviews with city officials. This co-produced research evolved out of conversations with city officials in Portland, Oregon, who were interested to learn how other cities were organising resilience work. Interviews focused on emerging definitions, organisational structures, internal and external coordination efforts, and practitioners’ insights. The paper includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…Thus, comparative studies of COVID-19 situation across cities can add knowledge to resilience framework regarding pandemic mitigation measures. Such evaluations would help city planners, policy-makers, and managers to understand better the current resilience level of cities against pandemic disasters ( Fastiggi, Meerow, & Miller, 2020 ; Hernantes, Maraña, Gimenez, Sarriegi, & Labaka, 2019 ; Scott, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, comparative studies of COVID-19 situation across cities can add knowledge to resilience framework regarding pandemic mitigation measures. Such evaluations would help city planners, policy-makers, and managers to understand better the current resilience level of cities against pandemic disasters ( Fastiggi, Meerow, & Miller, 2020 ; Hernantes, Maraña, Gimenez, Sarriegi, & Labaka, 2019 ; Scott, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has seven characteristics: reflexivity, inclusiveness, comprehensiveness, robustness, redundancy, flexibility, and resourcefulness (Paidakaki and Moulaert 2018 ). Urban resilience exists when the different subjects in the complex socioecological system of urban areas can successfully confront the various chronic and acute pressures that exist locally, such as natural disasters, economic crises, and social and political turbulence, through reasonable preparation and optimal coordination among system components (Fastiggi et al 2020 ). Thus, resilience includes the prevention, response, recovery, and long-term adaptation necessary to protect the public security, social order, and economic construction of urban areas from being affected.…”
Section: Introductionmentioning
confidence: 99%
“…However, to better understand or even support the institutionalisation of adaptive and networked governance strategies, both seem necessary. On the one hand, there is an ongoing thirst for knowledge about how exactly and under what circumstances different cities address the challenge of institutionalising urban and infrastructure resilience, thereby demanding qualitative and explorative case study research such as that reported in this thesis (Fastiggi et al, 2020). On the other hand, this study confirms other research findings that there is the need to somehow measure resilience (e.g.…”
Section: Reflections and Outlooksupporting
confidence: 79%
“…From a governance perspective, urban and infrastructure resilience stresses the need for collaboration and learning in multi-level, multi-sector, multi-actor and cross-territorial governance networks (Boyd and Juhola, 2015;Duit et al, 2010;Fastiggi et al, 2020;Goldstein, 2012;Goldstein and Butler, 2012;Ingold et al, 2018). This study provides an institutional perspective on the governance of urban and infrastructure resilience.…”
Section: Summary Of Resultsmentioning
confidence: 97%
See 1 more Smart Citation